2021
DOI: 10.7759/cureus.15981
|View full text |Cite
|
Sign up to set email alerts
|

Coaxial Double-Pigtail Stent Placement: A Simple Solution to Decrease Bleeding Risk Associated With Lumen-Apposing Metal Stent?

Abstract: Endoscopic cystogastrostomy using lumen-apposing metal stent (LAMS) is considered the first-line therapy for symptomatic pancreatic fluid collections (PFCs). Routine coaxial placement of a double-pigtail stent (DPS) through LAMS is debated. We report the case of a patient with delayed massive gastrointestinal bleed eight weeks after LAMS placement due to splenic artery pseudoaneurysm leading to a complicated hospitalization. Theoretically, coaxial placement of DPS through LAMS can prevent the relatively sharp … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In a study by Garcia-Alonzo et al, LAMS migration in patients undergoing PFC drainage was 21% 16 . A strategy that has been reported in the literature to decrease the risk of stent migration is placing a double-pigtail stent within the LAMS to help anchor the stent 18 19 . Shamah et al in a retrospective analysis of 68 patients comparing 35 patients with LAMS and DPS versus 33 patients with LAMS alone found no significant difference in AEs or clinical outcomes between the two groups 20 .…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Garcia-Alonzo et al, LAMS migration in patients undergoing PFC drainage was 21% 16 . A strategy that has been reported in the literature to decrease the risk of stent migration is placing a double-pigtail stent within the LAMS to help anchor the stent 18 19 . Shamah et al in a retrospective analysis of 68 patients comparing 35 patients with LAMS and DPS versus 33 patients with LAMS alone found no significant difference in AEs or clinical outcomes between the two groups 20 .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, use of coaxial DPS in LAMS has been suggested to minimize risk of bleeding complication reported with LAMS use for drainage of (peri)pancreatic collections. Theoretically, this technique might help by preventing direct contact of mucosa and surrounding blood vessels following collapse of (peri)pancreatic collection cavity and thus minimizing risk of vessel erosion and subsequent bleeding [ 43 ]. However, high-quality evidence to support its use is lacking, and retrospective studies with small sizes have reported conflicting results.…”
Section: Coaxial Dps In Lamsmentioning
confidence: 99%
“…The LAMS provides better anchorage, possibly reducing the migration rate, and allows access to the collections with the gastroscope through the stent to perform direct endoscopic necrosectomy. Furthermore, the use of the LAMS is safe with high clinical and technical success [ 5 , 6 ]. Among the various options of LAMS, the Hot-AxiosT system [ 7 ] is a practical and quick option for EUS drainage with a delivery system that allows the implantation of the stent in a short procedure time.…”
Section: Introductionmentioning
confidence: 99%